Aboriginal and Torres Strait Islander recruitment & career development strategy : survey report - Ella, Lyn.; Australian Library and Information Association (Kingston, ACT. : ALIA, 1996)
Survey results of Aboriginal and Torres Strait Islander people employed in the library and information sector in 1996.
"December 1996"
Includes bibliography.
Keywords: Minorities in library science -- Australia; Minority librarians -- Australia; Librarians -- Recruiting -- Australia; Aboriginal Australians -- Employment; Torres Strait Islanders -- Employment; Libraries; Occupations - Professional and technical workers; Employment - Discrimination - Anti discrimination measures